Implementasi Metode 360-Degree Feedback Sebagai Metode Evaluasi Kinerja Guru: Studi Kasus Pada Lembaga Pendidikan Keterampilan BBC Build Better Communitaion (LKP BBC) - Tsardosslapito; Pebriyanti, Mala; Supatrem, Supatrem (Innovative: Journal Of Social Science Research, 2025)
Teacher performance evaluation is a crucial element in improving the quality of education in training and course institutions. This study aims to describe the teacher performance evaluation process at BBC Build Better Communication using the 360-degree feedback model and to explain the relationship between the evaluation process and the institution’s quality objectives. This research employs a qualitative approach with data collection techniques including interviews and document analysis. The 360-degree feedback model enables a comprehensive assessment of teacher performance from various stakeholders, including students, colleagues, and management. The findings reveal that the teacher evaluation process at BBC is conducted systematically, considering pedagogical aspects, professionalism, and student satisfaction. Furthermore, teacher performance evaluation directly contributes to achieving the institution’s quality targets, particularly in enhancing learning quality and student satisfaction. This study highlights that the 360-degree feedback model can be an effective approach to assessing and developing teacher competencies in non-formal education settings.